A Curriculum for Master of Science in Physiology of Mbarara University of Science and Technology in Uganda - Valladares, Miriela Betancourt; Balaam, Kasiisi; Rosemary, Namayanja; Mukasa, Kiguli James; Freixas, José Luis Cadenas; Montero, Genny Dominguez; Nápoles, Marjories Mirabal; Manzanet, José Enrique Alfonso (Revista Cubana de Investigaciones Biomédicas, 2019)
New regulations together with the development of science and teaching demanded to write a curriculum for postgraduate training in Physiology in Mbarara University of Science and Technology (MUST). Objective: to design a Curriculum for Master of Science in Physiology at MUST. Methods: A qualitative study was conducted during one year under the guidance of the Curriculum Committee. The process was organized in three major phases: identification of needs and analysis of relevant documents; curriculum writing; assessment, review and submission. Some accomplished tasks included analysis of regulations, guidelines and other postgraduate curricula; identification of the learning needs and mandatory courses; designing of courses and other components, meetings, discussions and workshops; submissions and internal review. Relevant theoretical and empirical methods included analysis and synthesis; interviews; scientific observation; documents and bibliography review and experts consulting. This curriculum review process allowed to incorporate a new side to the previous programme: the teaching skills and aspects of Pathophysiology. Results: The curriculum was designed, presented, reviewed and approved to resume the training by the Department of Physiology, MUST and the first group of postgraduates started it in August 2016. Conclusions: the curriculum for Master of Science in Physiology, produced in less than one year of collective and intense work is being followed to train postgraduates at MUST. Without this curriculum, the training of Physiologists at MUST was not going to be possible despite the needs of the University and the region.
Keywords: Curriculum design; Postgraduate training; Learning needs; Physiology; Competencies